Quy trình thiết kế và tổ chức thực hành thí nghiệm nhằm phát triển năng lực tìm hiểu môi trường tự nhiên xung quanh cho học sinh trong dạy học Khoa học 4 - Hà , Văn Dũng; Phan , Thị Thùy Linh; Trương , Thị Thanh Mai (Tạp chí Giáo dục, 2024)
Practising experiments is one of the measures to stimulate students’ initiative, creativity, and independent thinking competence. Through practical activities, students will explore and discover phenomena in nature and life together. Grade 4 Science knowledge reflects natural objects such as Substance, Energy, Plants and animals, Fungi, bacteria, etc. Therefore, organizing teaching activities for these contents according to conducting experiments will contribute to developing the competence to learn about the surrounding nature, thereby contributing to the development of scientific competence for students. This article proposes a process for designing experimental teaching activities to develop students’ competence to learn about the surrounding natural environment and illustrates the process through an example of water permeability, under the topic “Water” (Science 4). The research results both complement and perfect the theory and contribute to concretizing practical issues about teaching and practicing experiments in high schools.